Skip to content
Snippets Groups Projects
Commit bc6ac19f authored by Olivier Blanvillain's avatar Olivier Blanvillain
Browse files

Add exercises/solutions-2.md

parent dddbcbc1
No related branches found
No related tags found
No related merge requests found
# Exercise 1 : Aggregate
## Question 1
- g(f(z, x1), f(f(z, x2), x3))
- g(f(f(z, x1), x2), f(z, x3))
- g(g(f(z, x1), f(z, x2)), f(z, x3))
- g(f(z, x1), g(f(z, x2), f(z, x3)))
## Question 2
Variant 1
This might lead to different results.
Variant 2
This might lead to different results.
Variant 3
This always leads to the same result.
Variant 4
This always leads to the same result.
## Question 3
A property that implies the correctness is:
```
forall xs, ys. g(xs.F, ys.F) == (xs ++ ys).F (split-invariance)
```
where we define
```
xs.F == xs.foldLeft(z)(f)
```
The intuition is the following. Take any computation tree for
`xs.aggregate`. Such a tree has internal nodes labelled by g and segments processed using `foldLeft(z)(f)`. The split-invariance law above says that any internal g-node can be removed by concatenating the segments. By repeating this transformation, we obtain the entire result equals `xs.foldLeft(z)(f)`.
The split-invariance condition uses `foldLeft`. The following two conditions together are a bit simpler and imply split-invariance:
```
forall u. g(u,z) == u (g-right-unit)
forall u, v. g(u, f(v,x)) == f(g(u,v), x) (g-f-assoc)
```
Assume g-right-unit and g-f-assoc. We wish to prove split-invariance. We do so by induction on the length of `ys`. If ys has length zero, then `ys.foldLeft` gives `z`, so by g-right-unit both sides reduce to xs.foldLeft. Let `ys` have length `n>0` and assume by I.H. split-invariance holds for all `ys` of length strictly less than `n`. Let `ys == ys1 :+ y` (that is, y is the last element of `ys`). Then
```
g(xs.F, (ys1 :+ y).F) == (foldLeft definition)
g(xs.F, f(ys1.F, y)) == (by g-f-assoc)
f(g(xs.F, ys1.F), y) == (by I.H.)
f((xs++ys1).F, y) == (foldLeft definition)
((xs++ys1) :+ y).F == (properties of lists)
(xs++(ys1 :+ y)).F
```
## Question 4
```scala
def aggregate[B](z: B)(f: (B, A) => B, g: (B, B) => B): B =
if (this.isEmpty) z
else this.map((x: A) => f(z, x)).reduce(g)
```
## Question 5
```scala
def aggregate(z: B)(f: (B, A) => B, g: (B, B) => B): B = {
def go(s: Splitter[A]): B = {
if (s.remaining <= THRESHOLD)
s.foldLeft(z)(f)
else {
val splitted = s.split
val subs = splitted.map((t: Splitter[A]) => task { go(t) })
subs.map(_.join()).reduce(g)
}
}
go(splitter)
}
```
## Question 6
The version from question 4 may require 2 traversals (one for `map`, one for `reduce`) and does not benefit from the (potentially faster) sequential operator `f`.
# Exercise 2 : Depth
## Question 1
Somewhat counterintuitively, the property doesn't hold. To show this, let's take the following values for *L1*, *L2*, *T*, *c*, and *d*.
```
L1 = 10, L2 = 12, T = 11, c = 1, and d = 1.
```
Using those values, we get that:
```
D(L1) = 10
D(L2) = max(D(6), D(6)) + 1 = 7
```
## Question 2
*Proof sketch*
Define the following function D'(L).
![](images/2-2.png)
Show that *D(L) ≤ D'(L)* for all *1 ≤ L*.
Then, show that, for any *1 ≤ L1 ≤ L2* we have *D'(L1) ≤ D'(L2)*. This property can be shown by induction on *L2*.
Finally, let *n* be such that *L ≤ 2n < 2L*. We have that:
```
D(L) ≤ D'(L) Proven earlier.
≤ D'(2n) Also proven earlier.
≤ log2(2n) (d + cT) + cT
< log2(2L) (d + cT) + cT
= log2(L) (d + cT) + log2(2) (d + cT) + cT
= log2(L) (d + cT) + d + 2cT
```
Done.
0% Loading or .
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment